Mmu-miR-199a-5p regulates CYP2B10 through repression of E4BP4 in mouse AML-12 hepatocytes. (3rd October 2021) - Ren, Shujing; Sun, Guanghui; Wu, Zhengping; Lin, Yanke; Wang, Shuai; Dong, Dong; Yu, Pei; Huang, Haiyan; Wu, Baojian
Abstract: miR-199a-5p is an important regulator of many biological processes. However, whether and how CYP enzymes are regulated by miR-199a-5p are unknown. Here, we aimed to investigate the potential role of mmu-miR-199a-5p in regulating CYP2 enzymes. Regulatory effects of mmu-miR-199a-5p on CYP expression were assessed in mouse AML-12 hepatocytes. The metabolic activity of CYP2B10 was probed using cyclophosphamide (CPA) as a specific substrate. The regulatory mechanism was investigated using combined luciferase reporter assays and chromatin immunoprecipitation. Of several important drug-metabolizing CYPs, mmu-miR-199a-5p significantly increased the mRNA levels of Cyp2a10, Cyp2c29, and Cyp2j5 in AML-12 cells with Cyp2a10 altered the most. Consistently, mmu-miR-199a-5p enhanced the expression of CYP2B10 protein and cellular metabolism of CPA. Based on database analysis, Cyp2b10 was not a direct target gene of mmu-miR-199a-5p. Thus, a mediator is necessary for the miRNA regulation of CYP2B10. We found that E4BP4 repressed Cyp2b10 transcription and expression through specific binding to a D-box element in the gene promoter. Moreover, mmu-miR-199a-5p inhibited the expression of E4bp4 at the posttranscriptional level by directly targeting the 59–65 nt segment in its 3′-UTR. In conclusion, mmu-miR-199a-5p positively regulates CYP2B10 expression through inhibiting its repressor E4BP4. Our findings may provide an increased understanding of the complex regulatory pathways for CYP2B10.